COVID-19, deforestation, and green economy - Singhal, Vibha; Jinger, Dinesh; Rathore, Avinash Chandra; Pal, Rama; Samal, Ipsita; Bhoi, Tanmaya Kumar; Paramesh, Venkatesh; Fahad, Shah; Jaremko, Lukasz; Abdelsalam, Nader R.; Jaremko, Mariusz (Frontiers in Forests and Global Change, 2024)
Corona has severely impacted many sectors in the past 2. 5 years, and forests are one of the major hits among all sectors affected by the pandemic. This study presents the consolidated data on deforestation patterns across the globe during COVID and also analyzes in depth the region-specific contributing factors. Exacerbated deforestation during COVID alarms biodiversity conservation concerns and pushes back the long-term efforts to combat pollution and climate change mitigation. Deforestation also increases the risk of the emergence of new zoonotic diseases in future, as deforestation and COVID are intricately related to each other. Therefore, there is a need to check deforestation and inculcation of conservation measures in building back better policies adopted post-COVID. This review is novel in specifically providing insight into the implications of COVID-19 on forests in tropical as well as temperate global regions, causal factors, green policies given by different nations, and recommendations that will help in designing nature-based recovery strategies for combating deforestation and augmenting afforestation, thus providing better livelihood, biodiversity conservation, climate change mitigation, and better environmental quality.